Effectiveness of the developed hot-work chair prototype for hot-work workers: a preliminary study in the view of ergonomics - Sanmugum, Sivabalan; Karuppiah, Karmegam; Samasivam, Sivasankar; How, Vivien; Rasdi, Irniza (Universiti Putra Malaysia, 2024)
Introduction: Workers in a selected company currently performing hot work using inadequate seating tools experience prolonged static and awkward body postures, leading to muscle discomfort and pain, especially in the buttocks, lower back, thighs, and other areas. This research aims to assess and compare the level of muscle discomfort between the control group, which continued their existing practices, and the experimental group, which used the newly developed hot work chair. Methods: The effectiveness of the hot work chair was evaluated using pre-test and post-test questionnaires, including a body discomfort chart assessed with a 100-millimeter Visual Analogue Scale (VAS). A total of 24 respondents were divided into two groups, with 12 respondents in each (control and experimental groups). The experimental group used the hot work chair, while the control group maintained their usual seating practices. Pre-tests and post-tests were conducted to assess muscle discomfort ratings before and after using the hot work chair. Results: Data analysis using the Wilcoxon signed-rank test revealed a significant difference in the overall discomfort rating for the experimental group between pre-test and post-test (Z = -3.062, p = 0.002). Conversely, there were no significant differences for the control group workers between the pre-test and post-test for the specified body regions. Notably, the highest discomfort ratings, such as buttocks, were reduced from 77.50 ± 4.78mm to 37.00 ± 4.13mm during the post-test. The experimental group showed an overall discomfort rating reduction of 49% after using the hot work chair. The chair’s seat, backrest, and knee support feature contoured cushions that adapt to various body postures, allowing multiple seating positions for users based on their requirements and working environment. Conclusion: The introduction of the hot work chair effectively reduced muscle discomfort during extended hot work activities and improved body postures, thereby potentially reducing the risk of muscle discomfort leading to musculoskeletal disorders and other work-related injuries.